Association of Serum Iron Parameters with Activity of Liver Enzymes in Mongolian Patients with Chronic Hepatitis "C" - Ganbold, Uugantsetseg; Dalkh, Tserendagva; Tsogbadrakh, Odgerel (Central Asian Journal of Medical Sciences, 2017)
Objectives: The purpose of this study was to investigate the relationship between serum iron parameters with the activity of liver enzymes among patients with HCV in Mongolia. Methods: Twenty patients with HCV, who were registered at the National Center for Communicable Diseases, Mongolia, participated in our study. Serum iron and serum ferritin levels were determined using immunoassay. Hepcidin levels were analyzed using ELISA. Results: Liver enzymes, aspartate aminotransferase (ASAT) and alanine transaminase (ALAT), were 65.79 ± 0.52u/l and 51.22 ± 0.54 u/l, respectively. Serum iron levels were high (>180μg/dl) in 20% of patients, while serum ferritin levels were high in (>300ng/ml) in 25% of patients. Serum ferritin levels were strongly correlated with elevated ASAT (r = 0.62, p = 0.005) and ALAT (r = 0.53, p = 0.02). Additionally, serum iron was strongly correlated with ASAT (r = 0.61, p = 0.002) and ALAT (r = 0.53, p = 0.02). No correlation was identified between ASAT or ALAT and hepcidin. Conclusion: ALAT and ASAT levels were directly associated with increased levels of serum iron, but not serum ferritin. Serum hepcidin levels may affect ASAT levels.